158: Dual Site Neonatal Intensive Care Unit Weekend On-Call Coverage – Does the Presence of a Second Attending Neonatologist on Weekends Alter Perceptions of Clinical Uncertainty, Patient Care and Education?. Issue 6 (1st June 2014) - Moore, G; Myron, H; Moreau, K
Abstract: BACKGROUND: The University of Ottawa has two level 3 NICUs, separated by an 8 min walk. In 2010, the on-call schedule changed from having one Attending Neonatologist on-call per weekend, to having two. This allowed for increased Attending supervision in each unit. OBJECTIVES: To examine the perceived impact of this schedule change on resident and fellow uncertainty, patient care, and teaching during weekends. DESIGN/METHODS: Residents, fellows, clinical assistants, nurses, and Attendings who had worked in the NICU before and after the change were surveyed. Because no survey tool existed, one was created based on domains published in the literature. The survey was piloted for content and readability. Responses were provided on a 5-point Likert scale. Results were analyzed using descriptive statistics and χ 2 test for associations. RESULTS: Ninety individuals were eligible. The response rate was 62% (n=56). Perceptions of patient care notably improved after the change, with 87% agreeing there was an improved ability to provide safer care, 81% of respondents believing that overall patient safety was improved, and 98% of respondents agreeing that care was timelier during weekend rounds. Eighty-eight percent of respondents perceived a moderate to great improvement in trainee certainty during clinical decision-making. Trainee certainty regarding the management of resuscitations was also improved (71% of respondents agreed). The respondents' clinical role affected their perceptions, with the greatest impact rated by the nurses, and the least by Attendings. CONCLUSIONS: Our results are the first to demonstrate that increased Attending supervision in the NICU decreases resident and fellow uncertainty. It may also improve patient care, and this warrants further objective study in the NICU setting. Results indicate support for one Attending per NICU in the case of two distinct physical sites.